(untitled) (Journal of Food and Dietetics Research, 2025)
Introduction: Adolescent girls are one of the most vulnerable groups for anemia. The high prevalence of anemia among adolescent girls is caused by various factors, including inadequate nutrition, gender disparities, poor sanitation and hygiene, and deeply rooted cultural and social norms. Therefore, anemia prevention and timely management require a broad, multi-dimensional approach that addresses these determinants. Objectives: The present study was conducted to assess the effectiveness of community-based intervention in improving knowledge, attitudes, practices, and norms among adolescent girls (15-19 years) in the selected blocks of the Gorakhpur district, Uttar Pradesh. Methods: A cross-sectional quantitative study was conducted in two intervention blocks (Khajani & Pipraich) of the Gorakhpur district. A baseline survey was followed by 5 months of intervention, after which an endline survey was conducted among unmarried adolescent girls (15-19 years). The baseline and endline surveys were conducted with a minimum of 400 adolescent girls. Moreover, the education intervention was conducted across 120-150 villages of the intervention district. The data were analyzed and presented as mean, and standard deviation (interquartile range), and frequencies (percentages) using STATA version 16.0. Results: The findings indicate a significant improvement in healthy eating intentions, perceived behavior control and social norms related to nutrition and anemia prevention from baseline to endline (p<0.05). We also noticed a statistically significant increase in knowledge, positive attitude, norms, and practices from baseline to end line. Conclusions: The present study suggests that community-based interventions are feasible strategiesfor improving aware ness, knowledge, attitudes, and behaviors among adolescents. Future interventions should incorporate components that target prevailing social norms, peer influence, and evidence-based behavior change strategies for sustainable outcomes. Keywords: Anemia, social norms, healthy eating, intentions